Method for producing composite particles, composite particles and mixture

JP7640546B2Active Publication Date: 2025-03-05DENKA CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2022530064
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-06-09
Filing Date
2021-05-10
Publication Date
2025-03-05
Estimated Expiration
2041-05-10

AI Technical Summary

Benefits of technology

【0009】 本発明の一側面によれば、ZnO、Al2O3及びSiO2の三成分を含有する粒子に関して、当該粒子を基材へ配合した際の基材の粘度を低くすることができる複合粒子及びその製造方法を提供できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007640546000002
    Figure 0007640546000002
  • Figure 0007640546000003
    Figure 0007640546000003
  • Figure 0007640546000004
    Figure 0007640546000004
Patent Text Reader

Abstract

This composite particle production method comprises a step (a) for mixing a raw material particle with at least one species of fine particle selected from an SiO2 fine particle and an Al2O3 fine particle and having a smaller particle diameter than the raw material particle, and a step (b) for heating the mixture of the raw material particle and the fine particle, wherein the raw material particle includes three components constituted by ZnO, Al2O3, and SiO2, with the ZnO content being 17 to 43% by mole, the Al2O3 content being 9 to 20% by mole, and the SiO2 content being 48 to 63% by mole, taking the total of the contents in the three components as the reference.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing composite particles, composite particles, and mixtures. [Background technology]

[0002] In general, various powdered fillers are used to improve the properties or functions of substrates such as glass materials and resin materials. For example, amorphous silica has a particle size of 0.5×10 -6 Since amorphous silica has a small thermal expansion coefficient of about 100 / °C and is relatively easily available, it is used as a filler for controlling the thermal expansion coefficient of a substrate. However, when it is added to a substrate used for bonding, sealing, encapsulation, etc., a filler with an even smaller thermal expansion coefficient than amorphous silica is desired in order to match the thermal expansion coefficient of the filler with that of the substrate and to suppress the occurrence of thermal stress.

[0003] Many materials, such as zirconium phosphate, zirconium tungstate, and manganese nitride, are known as materials with a smaller thermal expansion coefficient than amorphous silica. However, these materials have a large specific gravity, and the resin material etc. after mixing also becomes heavy, so they are not generally used in electronic parts etc. To compensate for this drawback, Patent Document 1 discloses SiO2-TiO2 glass, Li2O-Al2O3-SiO2 crystallized glass, and ZnO-Al2O3-SiO2 crystallized glass as materials that are lightweight and have a small thermal expansion coefficient. Patent Document 2 discloses inorganic powders having one or more crystal phases selected from β-eucryptite, β-eucryptite solid solution, β-quartz, and β-quartz solid solution. Non-Patent Document 1 also discloses Zn 0.5 AlSi2O6, LiAlSi2O6, and LiAlSiO4 are disclosed. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Japanese Patent Publication No. 2-208256 [Patent Document 2] JP 2007-91577 A [Non-patent literature]

[0005] [Non-Patent Document 1] Journal of Materials Science26 p.3051 (1991) Summary of the Invention [Problem to be solved by the invention]

[0006] When the above-mentioned filler is mixed with a base material such as a resin material, the viscosity of the base material after mixing can be reduced to improve the fluidity and moldability of the base material. In addition, by keeping the viscosity after mixing low, the filling rate of the filler can be increased, and the thermal expansion coefficient can be further reduced. However, in conventional fillers, there is still room for improvement in terms of reducing the viscosity of the base material after mixing.

[0007] One aspect of the present invention aims to provide composite particles containing three components, ZnO, Al2O3, and SiO2, that can reduce the viscosity of a base material when the particles are blended with the base material, and a method for producing the same. [Means for solving the problem]

[0008] The present invention provides a method for producing composite particles, composite particles, and a mixture as described below. (1) A method for producing composite particles, comprising: a step (a) of mixing raw material particles with at least one type of fine particles selected from SiO2 fine particles and Al2O3 fine particles having a particle size smaller than that of the raw material particles; and a step (b) of heating the mixture of the raw material particles and the fine particles, wherein the raw material particles contain three components, ZnO, Al2O3, and SiO2, and the ZnO content is 17 to 43 mol%, the Al2O3 content is 9 to 20 mol%, and the SiO2 content is 48 to 63 mol%, based on the total content of the three components. (2) The method according to (1), wherein in the step (a), the amount of the fine particles added is 4 parts by mass or less per 100 parts by mass of the raw material particles. (3) Composite particles comprising a core particle containing three components, ZnO, Al2O3 and SiO2, and at least one type of fine particles selected from SiO2 fine particles and Al2O3 fine particles fused to the surface of the core particle and having a particle diameter smaller than that of the core particle, wherein the core particle has a ZnO content of 17 to 43 mol%, an Al2O3 content of 9 to 20 mol%, and a SiO2 content of 48 to 63 mol%, based on the total content of the three components. (4) The composite particle according to (3), having an average circularity of 0.60 or more. (5) Composite particles according to (3) or (4), which contain 50 mass% or more of β-quartz solid solution as a crystal phase based on the total mass of the composite particles. (6) The composite particles according to any one of (3) to (5), wherein the content of Li, Na and K is each less than 100 ppm by mass based on the total amount of the composite particles. (7) The composite particle according to any one of (3) to (6), which is incorporated into glass or resin for use. (8) A mixture containing a first particle which is the composite particle according to any one of (3) to (7) and a second particle different from the first particle. (9) The mixture according to (8), wherein the average circularity of the second particles is 0.80 or more. (10) The mixture according to (8) or (9), wherein the content of the first particles is 10% by volume or more based on the total volume of the mixture. (11) The mixture according to any one of (8) to (10), wherein the second particles are SiO2 particles or Al2O3 particles. (12) The mixture according to any one of (8) to (11), which is incorporated into glass or a resin for use. Effect of the Invention

[0009] According to one aspect of the present invention, there is provided a composite particle containing three components, ZnO, Al2O3, and SiO2, which can reduce the viscosity of a base material when the particle is blended with the base material, and a method for producing the same. [Brief description of the drawings]

[0010] [Figure 1] 1 shows X-ray diffraction patterns of composite particles (particles) according to an example and a comparative example. [Diagram 2] 1 shows the results of SEM observation of composite particles (particles) according to Comparative Example 1 and Example 1. [Diagram 3] 1 shows the results of SEM observation of composite particles according to Examples 3 and 6. [Figure 4] 1 shows the results of SEM observation of composite particles according to Example 8. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Hereinafter, an embodiment of the present invention will be described, however, the present invention is not limited to the following embodiment.

[0012] A method for producing a composite particle according to one embodiment includes a step (a) of mixing raw material particles with at least one type of fine particles selected from SiO2 fine particles and Al2O3 fine particles having a particle size smaller than that of the raw material particles, and a step (b) of heating the mixture of the raw material particles and the fine particles. This production method can produce a composite particle (described in detail below) that includes a core particle containing three components, ZnO, Al2O3, and SiO2, and at least one type of fine particles selected from SiO2 fine particles and Al2O3 fine particles fused to the surface of the core particle.

[0013] In step (a), first, raw material particles are prepared. The raw material particles contain three components, ZnO, Al2O3, and SiO2. In one embodiment, step (a) may include a step of preparing raw material particles (raw material particle preparation step). Alternatively, raw material particles having the following features may be purchased and prepared.

[0014] In the raw material particle preparation process, first, raw materials are mixed to prepare a raw material mixture. The raw materials may be zinc oxide or the like as a Zn source, aluminum oxide or aluminum hydroxide or the like as an Al source, and silicon oxide (α-quartz, cristobalite, amorphous silica, etc.) as a Si source.

[0015] Regarding the amounts of the raw materials, based on the total amount of the Zn source, Al source and Si source raw materials, the amount of the Zn source may be 17 to 43 mol %, the amount of the Al source may be 9 to 20 mol %, and the amount of the Si source may be 48 to 63 mol %.

[0016] In the raw material particle preparation step, in addition to the above raw materials, a general nucleating agent such as zirconium oxide or titanium oxide may be added within a range that does not affect the thermal expansion coefficient.

[0017] In the raw material mixture, the content of ionic impurities is preferably as small as possible. The content of alkali metals contained in the raw material mixture is preferably 500 mass ppm or less, more preferably 150 mass ppm or less, further preferably 100 mass ppm or less, and particularly preferably 50 mass ppm or less, based on the total amount of the raw material mixture, from the viewpoint of improving the moisture resistance reliability and suppressing failures of electronic devices.

[0018] The method for mixing the raw material mixture is not particularly limited as long as it is a method that does not easily mix in alkali metals such as Na, Li, or K, and metal elements such as Fe. For example, the raw material mixture may be mixed using an agate mortar, a grinder such as a ball mill or a vibration mill, or various mixers.

[0019] In the raw material particle preparation process, the raw material mixture is then placed in a container such as a platinum crucible or an alumina crucible, and melted in a heating furnace such as an electric furnace, a high-frequency furnace, or an image furnace, or a flame burner. The melt is then taken out into air or water and quenched. This results in a raw material glass. The raw material glass obtained is pulverized to obtain raw material particles. The method for pulverizing the raw material glass is not particularly limited, and may be a method using an agate mortar, a ball mill, a vibration mill, a jet mill, a wet jet mill, or the like. The pulverization may be performed in a dry manner, or may be performed in a wet manner by mixing the raw material particles with a liquid such as water or alcohol.

[0020] By having the raw material particles have the above-mentioned composition, the thermal expansion coefficient of the base material containing the composite particles to be manufactured can be reduced. In addition, during the manufacturing of the particles, the raw material can be easily melted and crystallized. In particular, by having a composition with a ZnO content of 25 to 35 mol%, an Al2O3 content of 11 to 18 mol%, and an SiO2 content of 50 to 55 mol%, based on the total content of the three components, the thermal expansion coefficient of the base material containing the composite particles can be further reduced.

[0021] Step (a) may include a step of spheroidizing the raw material particles (spheroidizing step). In the spheroidizing step, the raw material particles are spheroidized by a so-called powder melting method. The spheroidizing method using the powder melting method is a method in which raw material particles are introduced into a chemical flame, a thermal plasma, a vertical tubular furnace, or a tower kiln, melted, and spheroidized by their own surface tension.

[0022] In the powder melting method, the particle size distribution after spheroidization can be adjusted by adjusting the particles obtained by pulverizing raw glass or raw material particles granulated by a spray dryer or the like to a desired particle size distribution. These raw material particles are charged into a chemical flame or thermal plasma, a vertical tubular furnace or a tower kiln, or the like while suppressing aggregation of the raw material particles, and melted to perform spheroidization. Alternatively, spheroidization may be performed by preparing a dispersion of raw material particles dispersed in a solvent or the like, spraying the liquid raw material using a nozzle or the like into a chemical flame or thermal plasma, a vertical tubular furnace or a tower kiln, etc., evaporating the dispersion medium, and then melting the raw material particles.

[0023] In the powder melting method, the chemical flame refers to a flame generated by burning a combustible gas with a burner. The combustible gas may be any gas that has a temperature equal to or higher than the melting point of the raw material particles, and may be, for example, natural gas, propane gas, acetylene gas, liquefied petroleum gas (LPG), hydrogen, or the like. Air, oxygen, or the like may be used as a combustion-supporting gas in combination with the combustible gas. The size, temperature, and other conditions of the chemical flame can be adjusted by the size of the burner and the flow rates of the combustible gas and the combustion-supporting gas.

[0024] In the raw material particles, the ZnO content is 17 to 43 mol %, the Al2O3 content is 9 to 20 mol %, and the SiO2 content is 48 to 63 mol %, based on the total content of the three components ZnO, Al2O3, and SiO2.

[0025] The content of ZnO is 17 to 43 mol% based on the total content of the three components, and from the viewpoint of reducing the thermal expansion coefficient of the base material, is preferably 20 to 40 mol%, more preferably 22 to 39 mol%, and even more preferably 25 to 35 mol%. The content of ZnO may be 17 to 40 mol%, 17 to 39 mol%, 17 to 35 mol%, 20 to 43 mol%, 20 to 39 mol%, 20 to 35 mol%, 22 to 43 mol%, 22 to 40 mol%, 22 to 35 mol%, 25 to 43 mol%, 25 to 40 mol%, or 25 to 39 mol% based on the total content of the three components.

[0026] The content of Al2O3 is 9 to 20 mol%, preferably 10 to 19 mol%, and more preferably 11 to 18 mol%, based on the total content of the three components. The content of Al2O3 may be 9 to 19 mol%, 9 to 18 mol%, 10 to 20 mol%, 10 to 18 mol%, 11 to 20 mol%, or 11 to 19 mol%, based on the total content of the three components.

[0027] The content of SiO2 is 48 to 63 mol%, preferably 49 to 62 mol%, more preferably 50 to 62 mol%, and even more preferably 50 to 55 mol%, based on the total content of the three components. The content of SiO2 may be 48 to 62 mol%, 48 to 55 mol%, 49 to 63 mol%, 49 to 55 mol%, or 50 to 63 mol%, based on the total content of the three components.

[0028] The particle diameter of the raw material particles is preferably 0.1 μm or more, more preferably 0.3 μm or more, even more preferably 0.5 μm or more, and is preferably 75 μm or less, more preferably 35 μm or less, even more preferably 10 μm or less. In this specification, the particle diameter of the raw material particles is the median particle diameter (D 50 ) The median particle size of the raw material particles means the 50% diameter (D50% diameter) in the cumulative fraction based on volume as specified in JIS R 1629. The dispersion treatment before measuring the median particle size of the raw material particles and the addition of the dispersion liquid to the measuring device are performed in the same manner as the method described in [Median particle size of composite particles] in the examples.

[0029] Next, the raw material particles (including the spheroidized raw material particles) are mixed with at least one type of fine particles selected from SiO2 fine particles and Al2O3 fine particles having a particle size smaller than that of the raw material particles. Here, "smaller in particle size than the raw material particles" refers to the median particle size (D 50 ) means that the specific surface area and particle size of the fine particles are smaller than that of the solid particles. The specific surface area and particle size of the fine particles are measured by the method described below.

[0030] The particle size of the fine particles is preferably 1 / 10 or less of the particle size (median particle size) of the raw material particles, more preferably 1 / 50 or less, and even more preferably 1 / 100 or less. The particle size of the fine particles may be, for example, 1 μm or less, 0.5 μm or less, or 0.1 μm or less, or may be 0.001 μm or more, 0.005 μm or more, or 0.01 μm or more. In this specification, the particle size of the fine particles means the specific surface area particle size of the fine particles.

[0031] In this specification, the specific surface area particle diameter d (m) is expressed by the true density of the fine particles ρ (g / cm 3 =100000×g / m 3 ), and the specific surface area is s (m 2 / g) and is calculated from d=6 / (ρ×s). The specific surface area of ​​the fine particles can be measured by the BET single point method using a specific surface area measuring device (for example, Mountech's "Macsorb HM model-1201 fully automatic specific surface area measuring device"). In this case, the degassing conditions during the measurement can be 200°C for 10 minutes, and the adsorption gas can be nitrogen. The true density of the fine particles can be measured by a gas (helium) substitution method using a dry densitometer (for example, Shimadzu's "Accupyk II1340").

[0032] The amount of the fine particles added is preferably 4 parts by mass or less relative to 100 parts by mass of the raw material particles. By not adding too much fine particles, the composite particles are favorably crystallized, and the fine particles are less likely to remain alone in the powder containing the composite particles, so that aggregation between the fine particles can be suppressed. As a result, the increase in viscosity when blended with the base material can be more effectively suppressed. The amount of the fine particles added is more preferably 3 parts by mass or less, even more preferably 2 parts by mass or less, and particularly preferably 1 part by mass or less relative to 100 parts by mass of the raw material particles, and is also preferably 0.1 parts by mass or more, and more preferably 0.2 parts by mass or more.

[0033] In step (b), the mixture of raw material particles and fine particles is heated to crystallize the raw material particles. Furthermore, this heating causes the fine particles to fuse to the surfaces of the crystallized raw material particles (core particles), thereby obtaining composite particles.

[0034] When using only raw material particles without using fine particles, the raw material particles may aggregate together after crystallization due to heating of the raw material particles. However, if the aggregates are forcibly broken down, broken particles are likely to be produced, making it difficult to effectively reduce the viscosity when the base material is mixed. On the other hand, in the manufacturing method of the present embodiment, composite particles in which fine particles are fused to the surface of the core particle can be obtained, so that the aggregation of the composite particles can be suppressed, and as a result, the increase in viscosity when the base material is mixed can be more effectively suppressed.

[0035] As the heating device for crystallization, any heating device may be used as long as the desired heating temperature can be obtained. For example, an electric furnace, a rotary kiln, a pusher furnace, a roller hearth kiln, etc. can be used.

[0036] The heating temperature (crystallization temperature) is preferably 750 to 900°C. By keeping the heating temperature within this range, the raw material particles can be crystallized while suppressing fusion between the raw material particles. In addition, the generation of a silica-rich crystalline phase or an alumina-rich crystalline phase derived from the fine particles can be suppressed as much as possible. This allows the content of β-quartz solid solution as a crystalline phase to be as large as possible, and also makes it easier to reduce the thermal expansion coefficient of the composite particles. In other words, by keeping the heating temperature within this range, it makes it easier to achieve both a reduction in the viscosity and the thermal expansion coefficient of the base material in which the composite particles are mixed.

[0037] The heating time (crystallization time) is preferably 1 to 24 hours. By setting the heating time to 1 hour or more, crystallization into the β-quartz solid solution phase is sufficiently performed, and the thermal expansion coefficient of the base material containing the composite particles can be further reduced. By setting the heating time to 24 hours or less, costs can be reduced.

[0038] Step (b) may include a step of crushing the powder of the composite particles by a method using an agate mortar, a ball mill, a vibration mill, a jet mill, a wet jet mill, or the like, if necessary. Crushing may be performed in a dry manner, or in a wet manner by mixing with a liquid such as water or alcohol. In the wet crushing, the composite particles of this embodiment are obtained by drying after crushing. The drying method is not particularly limited, and may be heat drying, vacuum drying, freeze drying, supercritical carbon dioxide drying, or the like.

[0039] In another embodiment, the method for producing composite particles may further include a step of classifying the composite particles so as to obtain a desired particle size (median particle size) and a step of surface treatment using a coupling agent. By carrying out the surface treatment, the amount of the composite particles to be mixed (loaded amount) in the base material can be further increased. The coupling agent used for the surface treatment is preferably a silane coupling agent. The coupling agent may be a titanate coupling agent or an aluminate coupling agent, etc.

[0040] By passing through step (b), composite particles having fine particles fused to the surface of the crystallized raw material particle can be obtained. That is, the composite particles obtained by the above-mentioned method include a core particle (crystallized raw material particle) containing three components, ZnO, Al2O3, and SiO2, and at least one kind of fine particles selected from fine particles of SiO2 and fine particles of Al2O3 having a particle size smaller than that of the core particle, fused to the surface of the core particle.

[0041] Here, "the particle size is smaller than that of the core particle" means that the particle size of the fine particles measured by electron microscopy is smaller than the particle size of the core particle measured by electron microscopy. The composite particles according to this embodiment are produced by the above-mentioned production method, and the specific surface area particle size of the fine particles is smaller than the median particle size of the raw material particles, so that the particle size of the fine particles measured by electron microscopy is also smaller than the particle size of the core particle in the composite particles.

[0042] In the composite particles, the fine particles are firmly fused to the surface of the core particles by the heating in step (b). This is a completely different aspect from the particles in a mixture obtained by simply mixing the core particles and the fine particles. The fact that the fine particles are fused to the core particles can be confirmed by observing that a plurality of fine particles are attached to the surface of the core particles when the composite particles are subjected to ultrasonic treatment for 3 minutes using an ultrasonic bath or ultrasonic homogenizer containing a solvent such as alcohol or acetone, and then one to several drops of this dispersion are dropped onto the sample stage of an electron microscope, and the composite particles are observed with a scanning electron microscope (SEM) after drying. In the case of a simple mixture of core particles and fine particles, even if fine particles are attached to the surface of the core particles, the fine particles are detached from the surface of the core particles by ultrasonic treatment. However, in the composite particles obtained by the above-mentioned method, the fine particles are firmly fused to the surface of the core particles, so that the fine particles are difficult to dissociate from the surface of the core particles even when ultrasonic treatment is performed.

[0043] In this composite particle, as described above, the fine particles are fused to the surface of the core particle, so that the aggregation of the composite particles is suppressed. Therefore, it is possible to suppress the increase in viscosity when the composite particles are blended as a filler in a base material such as a resin. If the increase in viscosity of the base material can be suppressed, more composite particles can be blended in the base material, and the thermal expansion suppression effect can be improved.

[0044] In the core particle, the ZnO content is 17 to 43 mol %, the Al2O3 content is 9 to 20 mol %, and the SiO2 content is 48 to 63 mol %, based on the total content of the three components ZnO, Al2O3, and SiO2.

[0045] The content of ZnO is 17 to 43 mol% based on the total content of the three components, and from the viewpoint of reducing the thermal expansion coefficient of the base material, is preferably 20 to 40 mol%, more preferably 22 to 39 mol%, and even more preferably 25 to 35 mol%. The content of ZnO may be 17 to 40 mol%, 17 to 39 mol%, 17 to 35 mol%, 20 to 43 mol%, 20 to 39 mol%, 20 to 35 mol%, 22 to 43 mol%, 22 to 40 mol%, 22 to 35 mol%, 25 to 43 mol%, 25 to 40 mol%, or 25 to 39 mol% based on the total content of the three components.

[0046] The content of Al2O3 is 9 to 20 mol%, preferably 10 to 19 mol%, and more preferably 11 to 18 mol%, based on the total content of the three components. The content of Al2O3 may be 9 to 19 mol%, 9 to 18 mol%, 10 to 20 mol%, 10 to 18 mol%, 11 to 20 mol%, or 11 to 19 mol%, based on the total content of the three components.

[0047] The content of SiO2 is 48 to 63 mol%, preferably 49 to 62 mol%, more preferably 50 to 62 mol%, and even more preferably 50 to 55 mol%, based on the total content of the three components. The content of SiO2 may be 48 to 62 mol%, 48 to 55 mol%, 49 to 63 mol%, 49 to 55 mol%, or 50 to 63 mol%, based on the total content of the three components.

[0048] The composite particles may contain ionic impurities, which are inevitable impurities, but in order to improve the moisture resistance reliability and suppress failure of electronic devices, the content is preferably as small as possible. Examples of ionic impurities include alkali metals such as Li, Na, and K. In the composite particles of this embodiment, the total content of Li, Na, and K is preferably less than 500 mass ppm, more preferably less than 300 mass ppm, and even more preferably less than 200 mass ppm based on the total amount of the composite particles.

[0049] The Li content is preferably less than 100 ppm by mass, more preferably less than 50 ppm by mass, and even more preferably less than 20 ppm by mass, based on the total amount of the composite particles. The Na content is preferably less than 100 ppm by mass, more preferably less than 90 ppm by mass, and even more preferably less than 80 ppm by mass, based on the total amount of the composite particles. The K content is preferably less than 100 ppm by mass, more preferably less than 70 ppm by mass, and even more preferably less than 40 ppm by mass, based on the total amount of the composite particles.

[0050] The composite particles may further contain zirconium oxide, titanium oxide, etc., within a range that does not affect the thermal expansion coefficient. From the viewpoint of further improving the effect of reducing the thermal expansion coefficient of the base material, the content of the above-mentioned three components is preferably 95 mol % or more, more preferably 98 mol % or more, and even more preferably 99 mol % or more, based on the total amount of the composite particles. From the same viewpoint, in one embodiment, the composite particles may be composed of only the above-mentioned three components and unavoidable impurities, or may be composed of only the above-mentioned three components.

[0051] The composite particles of this embodiment preferably contain β-quartz solid solution as a crystal phase. The composite particles may contain β-quartz solid solution as a main crystal. The content of the β-quartz solid solution is preferably 50% by mass or more, more preferably 60% by mass or more, and even more preferably 70% by mass or more, and may be 72% by mass or more, or 75% by mass or more, based on the total amount of the composite particles. The content of the β-quartz solid solution is preferably as high as possible. When the content of the β-quartz solid solution is in the above range, the thermal expansion coefficient of the composite particles themselves becomes small, so that the thermal expansion coefficient of the substrate can be further reduced. In particular, when the content of the β-quartz solid solution is 70% by mass or more, the reduction in thermal expansion of the substrate by the composite particles becomes more effective. Furthermore, the amount of the composite particles mixed (filling amount) in the substrate can be further increased, so that the thermal expansion coefficient of the substrate can be easily controlled. The structure of the β-quartz solid solution in the composite particles of this embodiment can be expressed as xZnO-yAl2O3-zSiO2. The identification of the crystalline phase and the measurement of the content can be carried out by powder X-ray diffraction measurement / Rietveld method.

[0052] The composite particles may further include an amorphous phase in addition to the β-quartz solid solution phase, and may further include other crystalline phases. The composite particles may include a willemite phase (Zn2SiO4) as the other crystalline phase. The composite particles may include a gahnite phase (ZnAl2O4), a mullite phase (Al6Si2O 13 ) and cristobalite phase (SiO2), the thermal expansion coefficient becomes relatively high, so the composite particles preferably do not contain these crystalline phases.

[0053] The shape of the composite particles is preferably as close to a sphere as possible. Whether the composite particles are substantially spherical or not can be confirmed by calculating the average circularity of the composite particles. The average circularity in this specification is calculated as follows. That is, the projected area (S) and projected perimeter (L) of the composite particles photographed using an electron microscope are calculated, and the circularity is calculated by applying them to the following formula (1). The average circularity is the average circularity of all particles included in an observation region of a certain area (an area including 100 or more particles). Circularity = 4πS / L 2 (1)

[0054] The average circularity is preferably as large as possible, preferably 0.60 or more, more preferably 0.70 or more, even more preferably 0.80 or more, particularly preferably 0.85 or more, and most preferably 0.90 or more. This reduces the rolling resistance of the particles when mixed with the base material, further reducing the viscosity of the base material and further improving the fluidity of the base material. In particular, when the average circularity is 0.90 or more, the fluidity of the base material is further increased, so that the composite particles can be further packed into the base material, and the thermal expansion coefficient can be easily reduced.

[0055] The particle size of the composite particles is not particularly limited, but considering that the composite particles are used as a filler to be blended with a base material, the particle size may be 0.5 to 100 μm, 1 to 50 μm, 1 to 40 μm, 1 to 30 μm, 1 to 20 μm, or 1 to 10 μm. In this specification, the particle size of the composite particles is defined as the median particle size (D 50 ) The median particle size of the composite particles means the 50% diameter (D50% diameter) in the cumulative fraction based on volume as specified in JIS R 1629. The dispersion treatment before measuring the median particle size of the composite particles and the addition of the dispersion liquid to the measuring device are performed in the same manner as the method described in [Median particle size of composite particles] in the examples.

[0056] The thermal expansion coefficient of the powder containing the composite particles is preferably as small as possible from the viewpoint of further reducing the thermal expansion coefficient of the base material containing the composite particles, and is preferably less than 2×10 -6 / °C or less, and more preferably 1×10 -6 / °C or less, and more preferably 0.5×10 -6 / ° C. or less. The thermal expansion coefficient can be measured by thermomechanical analysis (TMA).

[0057] A mixture can be obtained by using the above-mentioned composite particles and particles having a different composition from the above-mentioned composite particles. That is, the mixture according to one embodiment contains a first particle made of the above-mentioned composite particles and a second particle different from the first particle. By mixing the above-mentioned composite particles and the second particle, it is possible to more easily adjust the thermal expansion coefficient, thermal conductivity, filling rate, etc. when blended into a base material.

[0058] The second particles include inorganic oxide particles such as SiO2 and Al2O3. As SiO2 or Al2O3, those with higher purity are preferable. Since the thermal conductivity of SiO2 is small, when SiO2 particles are used as the second particles, the thermal expansion coefficient of the substrate can be further reduced. In addition, when Al2O3 is used as the second particles, the thermal conductivity of the substrate can be easily adjusted.

[0059] The shape of the second particles is preferably spherical. From the same viewpoint as the above-mentioned composite particles (first particles), the average circularity of the second particles is preferably as large as possible, and is preferably 0.80 or more, more preferably 0.85 or more, and even more preferably 0.90 or more. The average circularity of the second particles is calculated by the same method as the average circularity of the above-mentioned composite particles.

[0060] The particle size of the second particle (median particle size (D 50 In one embodiment, the particle diameter (median particle diameter (D )) of the second particles may be 0.01 μm or more, 0.05 μm or more, or 0.1 μm or more, and is preferably 3 μm or less, more preferably 2 μm or less, and even more preferably 1 μm or less. This makes it possible to further reduce the viscosity of the base material containing the mixture. 50 In another embodiment, from the same viewpoint, the diameter is preferably 10 μm or more, more preferably 20 μm or more, and further preferably 30 μm or more, and may be 100 μm or less, 90 μm or less, or 80 μm or less. The median particle diameter of the second particles means the 50% diameter (D50% diameter) in the volume-based cumulative fraction defined in JIS R 1629.

[0061] The content of the second particles in the mixture is preferably 90% by volume or less, more preferably 70% by volume or less, even more preferably 50% by volume or less, and particularly preferably 40% by volume or less, based on the total amount of the mixture. This makes it possible to more effectively reduce the thermal expansion coefficient of the base material. The content of the second particles may be 0.1% by volume or more, and is preferably 1% by volume or more.

[0062] From the viewpoint of effectively reducing the thermal expansion coefficient of the base material, the content of the first particles in the mixture is preferably 10% by volume or more, more preferably 30% by volume or more, even more preferably 50% by volume or more, and particularly preferably 60% by volume or more, based on the total amount of the mixture. The content of the first particles in the mixture may be, for example, 99.9% by volume or less, and is preferably 99% by volume or less, based on the total amount of the mixture.

[0063] The total amount of the first particles and the second particles in the mixture may be 90% by volume or more, 92% by volume or more, or 95% by volume or more, based on the total amount of the mixture. The mixture may consist of only the first particles and the second particles.

[0064] The mixture may further contain other particles having a composition different from that of the first particles and the second particles. When the second particles are particles of SiO2, the other particles may be particles of Al2O3. When the second particles are particles of Al2O3, the other particles may be particles of SiO2. The other particles may be, for example, at least one type of particles selected from the group consisting of zinc oxide, titanium oxide, magnesium oxide, and zirconium oxide. When the mixture contains other particles, the content of the other particles may be, for example, 0.1 to 10 volume % based on the total amount of the mixture.

[0065] The composite particles or mixture of this embodiment may be incorporated into a substrate for use. In one embodiment, the substrate may be glass. That is, one embodiment of the present invention may be a composition containing the composite particles and glass, or a composition containing the first particles, second particles, and glass. Types of glass include PbO-B2O3-ZnO, PbO-B2O3-Bi2O3, PbO-V2O5-TeO2, SiO2-ZnO-M, and the like. 1 2O series (M 1 2O is an alkali metal oxide), SiO2-B2O3-M 1 2O system, or SiO2-B2O3-M 2 O series (M 2 Examples of the glass include glasses having a composition such as O being an alkaline earth metal oxide.

[0066] In another embodiment, the substrate may be a resin. That is, one embodiment of the present invention may be a composition containing the above composite particles and a resin, or a composition containing the above first particles, the above second particles, and a resin.

[0067] The types of resin include epoxy resin, silicone resin, phenol resin, melamine resin, urea resin, unsaturated polyester, fluororesin, polyamide (polyimide, polyamideimide, polyetherimide, etc.), polybutylene terephthalate, polyester (polyethylene terephthalate, etc.), polyphenylene sulfide, wholly aromatic polyester, polysulfone, liquid crystal polymer, polyethersulfone, polycarbonate, maleimide-modified resin, ABS (acrylonitrile-butadiene-styrene) resin, AAS (acrylonitrile-acrylic rubber-styrene) resin, AES (acrylonitrile-ethylene propylene diene rubber-styrene) resin, etc. The substrate may be a mixture of these resins.

[0068] The amount (filling amount) of the composite particles or mixture in the substrate is appropriately selected depending on the physical properties such as the target thermal expansion coefficient, etc. The amount of the composite particles or mixture may be 30 to 95% by volume, and preferably 40 to 90% by volume, based on the total amount of the substrate after the addition of the composite particles or mixture.

[0069] When the mixture is blended into a base material, the mixing method may involve mixing the first particles and the second particles in the base material, or the first particles and the second particles may be mixed in advance and then blended into the base material.

[0070] By blending the composite particles or mixture of this embodiment into a substrate, the viscosity of the substrate after blending the composite particles or mixture can be reduced. The substrate blended with the composite particles or mixture of this embodiment has good flowability and excellent moldability due to its low viscosity. In addition, when blending the composite particles or mixture of this embodiment, the blending amount (filling rate) can be increased. EXAMPLES

[0071] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.

[0072] [Example 1] (Preparation of raw material particles) ZnO, Al2O3, and SiO2 were used as raw materials, and these raw materials were mixed in a vibration mixer (Lab RAM II, low-frequency resonant acoustic mixer manufactured by Resodyn). At this time, the raw materials were mixed so that ZnO was 28 mol%, Al2O3 was 18 mol%, and SiO2 was 54 mol% based on the total amount of these three components. 100 g of this mixture was placed in a platinum crucible and heated in an electric furnace to melt it. At this time, the temperature inside the electric furnace during melting was 1600°C, and the holding time at 1600°C was 30 minutes. After melting, the crucible was submerged in water and rapidly cooled to obtain raw material glass. The raw material glass was recovered from the platinum crucible and pulverized in a ball mill so that the median particle diameter was 10 μm or less, and a powder consisting of raw material particles was obtained. The median particle diameter (D 50 ) was 5 μm.

[0073] (Spheroidization treatment) The obtained raw material particles were fed into a high-temperature flame formed by LPG and oxygen gas using a carrier gas (oxygen) and spheroidized by the powder melting method, thereby obtaining spheroidized raw material particles.

[0074] (Addition of fine particles) For 100 parts by mass of the spherical raw material particles, SiO2 fine particles (AEROSIL 130, manufactured by Nippon Aerosil Co., Ltd., specific surface area 130 m 2 0.1 parts by mass of sintered carbide (particle size: 21 nm, specific surface area: 20 nm) was added.

[0075] (Crystallization) The mixture of raw material particles and fine particles was crushed and then placed in an alumina crucible, and crystallized in an air atmosphere using an electric furnace at a furnace temperature of 800° C. and a holding time at 800° C. for 1 hour. Thus, composite particles according to Example 1 were obtained.

[0076] [Examples 2 to 5] Composite particles according to Examples 2 to 5 were obtained in the same manner as in Example 1, except that the amount of SiO2 fine particles added per 100 parts by mass of raw material particles was changed to the amount shown in Table 1.

[0077] [Examples 6 to 10] The fine particles were changed from SiO2 to Al2O3 fine particles (AEROXIDE-Alu-C, manufactured by Nippon Aerosil Co., Ltd., specific surface area 100 m 2 The composite particles of Examples 6 to 10 were obtained in the same manner as in Example 1, except that the amount of Al2O3 fine particles added per 100 parts by mass of the raw material particles was changed to the amount shown in Table 1.

[0078] [Example 11] A powder made of raw material particles was obtained by the same method as in Example 1, except that ZnO, Al2O3, and SiO2 were mixed so that ZnO was 22 mol%, Al2O3 was 18 mol%, and SiO2 was 60 mol% based on the total amount of the three components. In addition, a composite particle according to Example 11 was obtained by the same method as in Example 1, except that the amount of SiO2 fine particles added per 100 parts by mass of raw material particles was changed to the amount shown in Table 1.

[0079] [Example 12] A powder made of raw material particles was obtained by the same method as in Example 1, except that ZnO, Al2O3, and SiO2 were mixed so that ZnO was 40 mol%, Al2O3 was 10 mol%, and SiO2 was 50 mol% based on the total amount of the three components. In addition, a composite particle according to Example 12 was obtained by the same method as in Example 1, except that the amount of SiO2 fine particles added per 100 parts by mass of raw material particles was changed to the amount shown in Table 1.

[0080] [Comparative Example 1] Particles according to Comparative Example 1 were obtained in the same manner as in Example 1, except that no fine particles were added to the raw material particles.

[0081] The properties of the produced composite particles or particles were evaluated by the following methods. The evaluation results are shown in Table 1.

[0082] [Identification of crystalline phases] Identification of the composite particles or the crystalline phase contained in the particles after crystallization and quantification of the content were performed by powder X-ray diffraction measurement / Rietveld method. A horizontal sample type multipurpose X-ray diffractometer (Rigaku Corporation, RINT-UltimaIV) was used as the device used, and measurements were performed under the conditions of an X-ray source of CuKα, a tube voltage of 40 kV, a tube current of 40 mA, a scan speed of 5.0° / min, and a 2θ scan range of 10° to 80°. X-ray diffraction patterns (excerpts) of the composite particles of Examples 2 to 4 are shown in FIG. 1(a), and X-ray diffraction patterns (excerpts) of the composite particles of Examples 6 to 8 are shown in FIG. 1(b). For comparison, X-ray diffraction patterns (excerpts) of the particles of Comparative Example 1 are shown in FIG. 1(a) and FIG. 1(b). For quantitative analysis of the crystalline phase, Rietveld method software (MDI Corporation, integrated powder X-ray software Jade+9.6) was used. The content b (mass%) of the β-quartz solid solution phase was calculated by the following formula (2) using the proportion a (mass%) of β-quartz solid solution obtained by Rietveld analysis after X-ray diffraction measurement of a sample in which α-alumina (internal standard substance), a standard sample for X-ray diffraction made by NIST, was added to the crystallized powder so that the content was 50 mass% (based on the total amount of the sample after addition). The crystal structure of the β-quartz solid solution of the obtained particles was calculated by the following formula (2) using the proportion a (mass%) of β-quartz solid solution obtained by Rietveld analysis with reference to conventional techniques (for example, Journal of Non-Crystalline Solids 351 149 (2005)). x / 2 Al x S 3-x Rietveld analysis was performed with the formula O6 (x = 1). Quantitative analysis of the crystal phase was performed for all examples and comparative examples. The results are shown in Table 1. b = 100a / (100-a) (2)

[0083] [Analysis of ZnO, Al2O3, SiO2 and quantification of impurities] The analysis of ZnO, Al2O3, and SiO2 (analysis of content) and the quantification of impurities were performed by inductively coupled plasma optical emission spectrometry. An ICP optical emission spectrometry analyzer (SPECTRO, CIROS-120) was used as the analytical device. In the analysis of ZnO, Al2O3, and SiO2, 0.01 g of composite particles was weighed into a platinum crucible, melted with a flux made of a mixture of potassium carbonate, sodium carbonate, and boric acid, and then dissolved by adding hydrochloric acid to prepare a measurement solution. In the analysis of impurities, 0.1 g of composite particles was weighed into a platinum crucible, and hydrofluoric acid and sulfuric acid were used to perform pressure acid decomposition at 200°C to prepare a measurement solution.

[0084] [Average circularity] Powder consisting of composite particles was fixed to a sample stage with carbon tape, and then osmium-coated. Images of 2048 x 1356 pixels at 500 to 5000 times magnification taken with a scanning electron microscope (JEOL, JSM-7001F SHL) were imported into a personal computer. The particles analyzed by image analysis were in the range of 1 μm to 10 μm. This image was used with an image analyzer (Nippon Roper, Image-Pro Premier Ver. 9.3) to calculate the projected area (S) and projected perimeter (L) of the composite particle, and then the circularity was calculated using the following formula (1). The circularity of all particles in an observation area containing 100 or more composite particles was calculated, and the average value was taken as the average circularity. Circularity = 4πS / L 2 (1)

[0085] [Median particle size of composite particles] The median particle size was measured using a laser diffraction particle size distribution analyzer (Beckman Coulter, LS 13 320). 31000g of pure water and 0.1g of the composite particles obtained were placed in a container, and dispersed for 1 minute using an ultrasonic homogenizer (BRANSON, SFX250). The dispersion of the composite particles that had been dispersed was added drop by drop to a laser diffraction particle size distribution analyzer, and measurements were taken 30 seconds after the specified amount was added. The particle size distribution was calculated from the data on the light intensity distribution of diffracted / scattered light by the particles detected by a sensor in the laser diffraction particle size distribution analyzer. The median particle size of the composite particles was calculated as the 50% diameter (D50% diameter) in the cumulative fraction based on volume as specified in JIS R 1629.

[0086] [Observation of the shape of composite particles] Each composite particle or particle of Examples 1, 3, 6, 8, and Comparative Example 1 was observed using a scanning electron microscope (SEM). The observation results are shown in Figures 2 to 4. As shown in Figures 2 to 4, in the composite particles of Examples 1, 3, 6, and 8 to which fine particles were added, it was observed that the fine particles were fused to the surface of the core particle. On the other hand, in the particle of Comparative Example 1 to which no fine particles were added, fusion of the fine particles was not observed.

[0087] [viscosity] The composite particles were mixed with bisphenol A liquid epoxy resin (Mitsubishi Chemical Corporation, JER828) so that the composite particles accounted for 50% by volume of the total, and kneaded with a planetary mixer (Thinky Corporation, "Awatori Rentaro AR-250", rotation speed 2000 rpm) to prepare a resin composition. The viscosity of the obtained resin composition was measured under the following conditions using a rheometer (Nihon SiberHegner AG, MCR-300). The viscosity of the resin composition using the particles of Comparative Example 1 was set as 100, and the relative viscosity (relative viscosity) of the resin composition using the composite particles of each Example was determined. Plate shape: circular flat plate 25mmφ Sample thickness: 1mm Temperature: 25±1℃ Shearing speed: 1s -1

[0088] [Table 1] [Industrial Applicability]

[0089] The composite particles obtained by the production method according to the present invention can be used as a filler that can lower the thermal expansion coefficient of a substrate, such as glass, resin, etc., when filled into the substrate. Furthermore, the substrate containing the composite particles of the present invention has low viscosity and high fluidity, and can therefore be used as a filler that can be highly filled.

Claims

1. A step (a) of mixing raw material particles with fine particles of Al 2 O 3 having a particle size smaller than that of the raw material particles; and (b) heating the mixture of the raw material particles and the fine particles, The raw material particles are ZnO, Al 2 O 3 and SiO 2 The content of the ZnO is 17 to 43 mol %, and the content of the Al is 17 to 43 mol %, based on the total content of the three components. 2 O 3 The content of SiO is 9 to 20 mol %, 2 The content is 48 to 63 mol %, the amount of the fine particles added is 0.2 parts by mass or more and 1 part by mass or less with respect to 100 parts by mass of the raw material particles, The fine particles have a particle diameter of 0.01 μm or more and 0.1 μm or less, The composite particles have a particle diameter of 1 to 10 μm and an average circularity of 0.90 or more.

2. ZnO, Al 2 O 3 and SiO 2 A core particle containing the three components; and Al 2 O 3 fine particles fused to the surface of the core particle and having a particle diameter smaller than that of the core particle. In the core particle, the content of the ZnO is 17 to 43 mol %, and the content of the Al is 17 to 43 mol %, based on the total content of the three components. 2 O 3 The content of SiO is 9 to 20 mol %, 2 The content is 48 to 63 mol %, the amount of the fine particles added is 0.2 parts by mass or more and 1 part by mass or less with respect to 100 parts by mass of the core particles, The fine particles have a particle diameter of 0.01 μm or more and 0.1 μm or less, The composite particles have a particle diameter of 1 to 10 μm and an average circularity of 0.90 or more.

3. 3. The composite particle according to claim 2, which contains 50 mass % or more of a β-quartz solid solution as a crystal phase based on the total mass of the composite particle.

4. The composite particle according to claim 2 or 3, wherein the content of Li, Na and K is each less than 100 ppm by mass based on the total amount of the composite particle.

5. The composite particle according to any one of claims 2 to 4, which is incorporated into glass or resin for use.

6. A mixture comprising a first particle which is the composite particle according to any one of claims 2 to 5, and a second particle different from the first particle.

7. 7. The mixture of claim 6, wherein the second particles have an average circularity of 0.80 or more.

8. The mixture according to claim 6 or 7, wherein the content of the first particles is 10% by volume or more based on the total amount of the mixture.

9. The second particles are SiO 2 Particles of Al 2 O 3 The mixture according to any one of claims 6 to 8, which is a particle of

10. The mixture according to any one of claims 6 to 9, which is incorporated into glass or resin for use.

Citation Information

Patent Citations

  • Low thermal expansion ceramics and filling material for sealing semiconductor

    JP1990208256A

  • Inorganic substance powder and composite material using the same

    JP2007091577A

  • Inorganic filler particle and resin composition for solid molding

    JP2017007921A

  • Powder and mixed powder

    WO2019177112A1